Corruption - An Inhibiting Factor for the Efficient Implementation of Structural Funds in Romania - Andrei Sebastian Badea (CES Working Papers, 2012)
The aim of this paper is to give an insight into the link between corruption and the implementation of structural and cohesion funds in Romania and the other Central and Eastern European states (CEE). Although there is a great interest within the mass-media and the civil society for this topic, very few in-depth analyses have been carried out on this subject by independent researchers. This article starts with an evaluation on the various indicators and indexes that quantify corruption, continuing with a comparison at a regional level. Afterwards, the analysis continues with a brief assessment on the implementation of structural funds in Romania and the other CEE states. What we have found by analysing the corruption indices and absorption rates for 7 European Union member states is that there is a strong link between the two phenomena: states with high levels of corruption benefit less from structural and cohesion funds having lower absorption rates.
Keywords: D73; E61; O52; R11; R58; 330; Structural funds; Cohesion Funds; Corruption in Romania Romania